Prevention of Non-Procedural Labour Migration in Ende Regency: Strategies, Challenges and Cross-Sector Collaboration - Helenerius Ajo Leda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Nonprocedural labor migration in Ende Regency is a serious problem that has an impact on workers' vulnerability to exploitation and rights violations. The background of this study is based on the high rate of illegal migration and the weak understanding of the community about official migration procedures. The purpose of this study is to identify forms of nonprocedural migration prevention carried out by the local government and strategic partners, and to evaluate the challenges faced in its implementation. This study uses a descriptive qualitative method with data collection techniques through interviews and documentation. Data analysis was carried out in stages, starting from organizing data, thorough reading, coding processes based on prevention themes, compiling descriptions, to interpreting data related to migration policy literature. The results of the study indicate that prevention efforts are carried out through regulatory, protective, and collaborative approaches. The strategies implemented include socialization, education, the formation of the TPPO Task Force, supervision of P3MI companies, and the active involvement of the KKP-PMP of the Archdiocese of Ende through the migrant-friendly parish program and facilitation of civil documents. However, the main challenges faced are the lack of regional regulations, minimal data on non-procedural migrants, and low public understanding. Therefore, the recommendations provided include strengthening regulations, increasing bureaucratic capacity, and developing cross-sector collaboration. Further research is needed to evaluate the effectiveness of the program and explore socio-cultural factors that influence non-procedural migration.